Atendimento operacional em ti: fordismo ou pós-fordismo? Estudo de caso na empresa Dataprev - Lavinas, Antônio David Ribeiro (2009)
The goal of this study is to analyse if the main changes ocurred in the form of conduction of an operational management process of a TI public company, regarding the implantation of a new model of technical support to the users of their products and services made a change in the paradigm of the existing management. According to these, the adopted path for this study was to search for any alteration related to the procedures of organization and management of the activities and not the ones related to the technical infrastructure. With this, it was used as a theoretical reference the literature that englobes the evolution's progress of the management production, specially those developed at the end of the 19's century until the present days, such as taylorism, fordism and post-fordism. For structuring the information data, the following analysis dimensions were defined: The Knowledge of the Process; The Production's Planning; Implementation of Production, Process Control, Division of Labor, Work in Team and Technical Resources, applied to any model, allowing the comparison among these. For data rasing, there were used the existing documentation of the company, registers from the data base, direct observation, participants' observation and questionaries, answered by the managers responsible for the conduction of the process. Once finished this part, and with the use of the analysis dimensions, there were identified the main characters of both adopted paradigms: fordism and pos-fordism. There were also descriptions of these analysis dimensions considering the collected data about the models in study. Finally there was the confrontation of information to identify which model most closely resembles each model and whether the change envisaged. The results showed that the previous model was closest to the Fordist paradigm, while the new model showed its main features identified with the post-Fordist paradigm. This was possible to conclude that the proposed research done in this work showed that the model adopted promotes change in the paradigm of management in the previous model.